2017
DOI: 10.3389/fncel.2017.00386
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Gene Expression Provides New Insights into the Effect of Mild Therapeutic Hypothermia on Primary Human Cortical Astrocytes Cultured under Hypoxia

Abstract: Hypothermia is increasingly used as a therapeutic measure to treat brain injury. However, the cellular mechanisms underpinning its actions are complex and are not yet fully elucidated. Astrocytes are the most abundant cell type in the brain and are likely to play a critical role. In this study, transcriptional changes and the protein expression profile of human primary cortical astrocytes cultured under hypoxic conditions for 6 h were investigated. Cells were treated either with or without a mild hypothermic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 98 publications
(113 reference statements)
0
35
1
Order By: Relevance
“…Increasing evidence suggests that AD pathogenesis is not restricted to the neuronal compartment. Glial cells, particularly reactive astrocytes and activated microglia, appear to play critical and interactive roles in neurodegeneration [22,23]. Accumulating evidence of their role in brain energy metabolism and reduced oxygen supply to the brain clearly point to their critical involvement in the prevention, initiation, and progression of neurodegenerative diseases, including AD [10,24].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that AD pathogenesis is not restricted to the neuronal compartment. Glial cells, particularly reactive astrocytes and activated microglia, appear to play critical and interactive roles in neurodegeneration [22,23]. Accumulating evidence of their role in brain energy metabolism and reduced oxygen supply to the brain clearly point to their critical involvement in the prevention, initiation, and progression of neurodegenerative diseases, including AD [10,24].…”
Section: Discussionmentioning
confidence: 99%
“…Glial cells and neuroinflammation may have a critical role in the prevention, but also initiation and progression of AD [54] interfering in multiple brain functions as energy metabolism [3]. They are involved in the maintenance of the CNS homeostasis and protection from various stresses (i.e., hypoxia) by providing metabolic and structural support [55]. Regarding the role of IL-6 trans-signaling, previous studies demonstrated decreased neuroinflammation, including IL-6 production, in response to peripheral LPS if sgp130 is administered icv [56]; and using the same GFAP-sgp130Fc, a prominent down-regulation of the neuroinflammation caused by the transgenic expression of IL-6 was observed [24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we acknowledge that hypothermia may have contributed to the gene expression patterns. Although we cannot completely exclude that some of the differentially expressed genes were stimulated by hypothermia, preclinical evidence has shown that a reduction by 4–10°C for over 6 h was required to influence gene expression in animal models [28-32]. Moreover, none of the hypothermia-inducible genes were found to be significantly differently expressed between neonatal encephalopathy and control babies [33].…”
Section: Discussionmentioning
confidence: 99%